(untitled) (Web of Teachers: Inderscience Research, 2024)
Innovations in enduring technologies such as wearable touch gadgets, sensor devices, and wireless private communication networks are connecting things in everyday life to the Internet, commonly referred to as the Internet of Things (IoT). IoT is seen as an active organization for the design and development of intelligent and contextual services and applications in the fields of business, science, and engineering. These apps and services can respond strongly to changes around them and user preferences. Developing a large-scale system for analyzing, processing, and mining huge real-world-based data sets has become one of the demanding challenges facing systems researchers and data management researchers. The use of big data analytics with IoT technologies is one of the ways to analyze data flows (i.e., data, events) in real-time. In this article, we propose an integrated approach that integrates IoT systems with big data tools into a holistic platform for real-time and continuous data monitoring and processing.